A feasibility study of multislice X‐ray CT imaging of gel dosimeters using the "zero scan" method. (8th July 2014) - Kakakhel, Muhammad B.; Kairn, Tanya; Charles, Paul; Trapp, Jamie V.
Abstract : This study extends the 'zero scan' method for CT imaging of polymer gel dosimeters to include multislice acquisitions. Multislice CT images consisting of 24 slices of 1.2 mm thickness were acquired of an irradiated polymer gel dosimeter and processed with the zero scan technique. The results demonstrate that zero scan‐based gel readout can be successfully applied to generate a three‐dimensional image of the irradiated gel field. Compared to the raw CT images, the processed figures and cross‐gel profiles demonstrated reduced noise and clear visibility of the penumbral region. Moreover, these improved results further highlight the suitability of this method in volumetric reconstruction with reduced CT data acquisition per slice. This work shows that 3D volumes of irradiated polymer gel dosimeters can be acquired and processed with X‐ray CT. PACS number: 87.57.Q‐, 87.57.nf, 87.55.‐x